The YAP1/SIX2 axis is required for DDX3-mediated tumor aggressiveness and cetuximab resistance in KRAS-wild-type colorectal cancer - Wu, De-Wei (Theranostics, 2017)
The mechanism underlying tumor aggressiveness and cetuximab (CTX) resistance in KRAS-wild-type (KRAS -WT) colorectal cancer remains obscure. We here provide evidence that DDX3 promoted soft agar growth and invasiveness of KRAS-WT cells, as already confirmed in KRAS-mutated cells. Mechanistically, increased KRAS expression induced ROS production, which elevated HIF-1α and YAP1 expression. Increased HIF-1α persistently promoted DDX3 expression via a KRAS/ROS/HIF-1α feedback loop. DDX3-mediated aggressiveness and CTX resistance were regulated by the YAP1/SIX2 axis in KRAS-WT cells and further confirmed in animal models. Kaplan-Meier and Cox regression analysis indicated that DDX3, KRAS, and YAP1 expression had prognostic value for OS and RFS in KRAS-WT and KRAS-mutated tumors, but SIX2 and YAP1/SIX2 were prognostic value only in KRAS-WT patients. The observation from patients seemed to support the mechanistic action of cell and animal models. We therefore suggest that combining YAP1 inhibitors with CTX may therefore suppress DDX3-mediated tumor aggressiveness and enhance CTX sensitivity in KRAS-WT colorectal cancer.